Toxic and latent effect of three isolated botanical chemicals on the Egyptian cotton leafworm, Spodoptera littoralis (boisd).noctuidae:Lepidoptera - Abdel-Rahim, Elham F. M.; Ahmed, M. E. M. (2008)
The toxic effect of three chemicals ,were isolated from plants, Anaphalis margaotacea, Chenopodium ambrosioides and Ambrosia maritime against the second and fourth instar larvae of the cotton leafworm, Spodoptera /ittora/is was bioassayed In the laboratory tests. The molecular formula of these chemicals were Cb15(BHb12(BOb4(B,Cb27(BHb30(BOb14 (Band Cb18(BHb16(BOb7 (B,respectively .s
Includes reference.
Summary in arabic.
1
Keywords: Cotton leafworm -- Control; Botanical insecticides; Neem insecticide